2016
DOI: 10.2147/cia.s105652
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of quality of life among hospitalized geriatric patients with diabetes mellitus upon discharge

Abstract: PurposeDiabetes mellitus is prevalent among older adults, and affects their quality of life. Furthermore, the number is growing as the elderly population increases. Thus, this study aims to explore the predictors of quality of life among hospitalized geriatric patients with diabetes mellitus upon discharge in Malaysia.MethodsA total of 110 hospitalized geriatric patients aged 60 years and older were selected using convenience sampling method in a cross-sectional study. Sociodemographic data and medical history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Diabetes had the least negative influence on the "people's reactions" domain [6,7,22]. It was found that the worse QoL of patients with diabetes was associated with the occurrence symptoms of depression [8,10,15,20,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes had the least negative influence on the "people's reactions" domain [6,7,22]. It was found that the worse QoL of patients with diabetes was associated with the occurrence symptoms of depression [8,10,15,20,24].…”
Section: Introductionmentioning
confidence: 99%
“…Studies applying the ADDQoL scale, which was verified among many populations differing in terms of culture, ethnicity and the environment, were carried out in both types of diabetes in many countries, i.e. England [3], Slovenia [6], Greece [7], Turkey [14], Romania [8], Portugal [19], Korea [15], Taiwan [5,16], China [17], Malaysia [13,20], Chinese-speaking participants in Singapore [21], Argentina [9], Australia [12], and north-eastern United States (among Spanish-speaking patients of Puerto-Rican nationality residing there) [10]. It was found that in societies inhabiting various parts and regions of the world the influence of diabetes on particular domains of the QoL of persons with this disease was differentiated.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies, including here randomized clinical trials, described the influence of several factors that had an impact on the QoL in cohorts of patients diagnosed with both type 2 diabetes mellitus (T2DM)12,13 and type 1 diabetes mellitus (T1DM);14 however, there were observed significant differences regarding the importance and impact on QoL of different factors, differences generated mainly by regional, geographical, and cultural differences between the studied cohorts. Emphasized by this fact and considering that the Romanian patients have a set of cultural and social particularities, we considered that studying these factors and their impact on Romanian patients’ QoL is of paramount importance.…”
Section: Introductionmentioning
confidence: 99%
“…with T2DM [4] [5]. Health-related quality of life (HRQoL) is an individual's assessment of the welfare conditions related to health [6].…”
Section: Introductionmentioning
confidence: 99%
“…Several randomized clinical trials described the effect of various factors on the quality of life (QoL) of patients diagnosed with T2DM [ 4 ] [ 5 ]. Health-related quality of life (HRQoL) is an individual’s assessment of the welfare conditions related to health [ 6 ].…”
Section: Introductionmentioning
confidence: 99%